PRAXEOLOGICAL ORGANIZATION OF SIMILARITY TASKS IN JUNIOR HIGH SCHOOL TEXTBOOKS ACROSS FOUR CURRICULA - Dora Anggraini; Dyana Wijayanti (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze similarity task in Indonesian junior high school mathematics textbooks from four different curricula: KTSP, the 2013 Curriculum, the Revised 2013 Curriculum, and the Merdeka Curriculum, using the praxeological organization approach within the framework of the Anthropological Theory of the Didactic (ATD). The research employed a qualitative approach using a document analysis method. The subjects of the study were similarity related problems found in junior high school mathematics textbooks published by the Indonesian government, across four different curricula. Coding techniques were used as the research instrument to gather empirical data about textbook praxeology organization structures, while the analysis instrument interpreted the didactic organization between praxis elements: types of task (T) and technique (τ). The study identified nine types of task (T1-T9) and nine corresponding techniques (τ1 - τ9), which vary across curricula. A significant reduction in the number of type odf tasks was found in the Merdeka Curriculum textbook, indicating a shift in curricular focus concerning numeracy. These findings reveal that the variation in problem types and presentation approaches in textbooks is closely related to curriculum changes. This aligns with the role of textbooks as blueprints of the curriculum. Therefore, this research contributes to the development of mathematics pedagogy and provides valuable insights for teachers, textbook authors, and policymakers in designing more effective learning experiences. Keywords: organizational praxeology, similarity, textbook, curriculum, ATD